Peranan Istitusi dalam Meningkatkan Kualitas Sumber Daya Manusia di Politeknik Negeri Bandung - Mia Rosmiati (Social and Political Science Faculty - Universitas Tidar, 2020)
This research was conducted to analize the role of the Bandung State Polytechnic (Polban) institution in order to improve the quality of policy makers, lecturers and educational staff and students. The method used is a qualitative research design, because the researcher seeks to observe and reveal what is happening in reality and will further observe and explore the behavior of the object being studied. The results of this study indicate that Polban has carried out many activities or work programs that are devoted to the development and improvement of human resources in the campus environment, in order to reach the goals that accordance with the vision and mission of the Polban institution so that Polban’s human resources can be competitive in any field, especially the ability in information technology systems. The conclusion from this research is that institutions have a big role in improving the quality of their human resources, and this requires high commitment from policy makers where top level management plays an important role in the decision-making process regarding policies to be implemented in the Polban environment in order to achieve the goal of improving quality of human resources.